COVID-19 and Dispositions of the Chilean Healthcare System: Sociomedical Networks in Care Decisions of Chronic Illnesses - Schöngut-Grollmus, Nicolás; Energici, María-Alejandra; Zuñiga, Natalia (Frontiers in Sociology, 2021)
This article is an empirical work on medical decisions in the case of chronic illnesses during the COVID19 pandemic context. Medical decisions are processes that guide the production of a health diagnosis or treatment, using the available information, where the patients’ preferences are often incorporated. This article tackles the impact of the pandemic in chronically ill patients’ medical decisions when the care system has been significantly altered by it. Considering that health decisions are importantly embedded in social and economic conditions, the pandemic affects a precarious care system and sustains individual possibilities. Chile has a weak support infrastructure for caregivers and a health care system that promotes private health and a low-quality public health system. Hence the pandemic is an adverse context for chronically ill patients and it alters the conditions in which to take medical decisions. We performed ten interviews with chronically ill patients who took responsibility for their own health decisions: five patients diagnosed with common chronic diseases and five patients diagnosed with rare chronic diseases. Using Reflexive Thematic Analysis, the results show that the Chilean health system is extremely precarious and that not many alternatives are or have been offered to chronically ill patients in the COVID19 context.